INCOME ANALYSIS OF MAIZE FARMERS ON RUBBER PLANTATION HIATEN LAND UTILIZATION SUNGEI PUTIH RESEARCH UNIT - Ginting, Trydha Yanti; Mastuti, Rini; Supristiwendi, Supristiwendi; Bulkaini, Bulkaini (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Sungei Putih Research Unit is an area located in Galang District, Deliserdang Regency which has a rubber plantation sector. The vacant land found in rubber plantations in this area is used by the community, one of which is to grow corn. The purpose of this research is to increase the income of corn farmers through the use of land between rubber plantations in Sungei Putih Research Unit and to evaluate the advantages and disadvantages of corn farming by utilizing land using the R/C Ratio and ROI. This research was conducted at Sungei Putih Research Unit, Galang District, Deli Serdang Regency using the Saturated Sampling method to select 9 farmers who intercropped rubber with corn as research samples. To find out whether the business is profitable or not, production costs and income are calculated and then analyzed using the R/C Ratio and ROI, and the income contribution is calculated. The results showed that the R/C ratio was 2.36 > 1, which means that every production cost of Rp. 1,000 will generate income of Rp. 2,360 for farmers so that corn farming on rubber plantations between Sungei Putih Research Unit is profitable. The ROI value of 36.66% indicates that farming has a profitable profit rate, and a revenue contribution of 69.39% indicates that corn farming on rubber plantation land makes a good contribution to the total income of farmers. To increase the maximum income, it is recommended that farmers take good care of their corn plants so that they are free from pests and diseases.